Ionic liquid-responsive phase transfer of gold nanoparticles: anionic metathesis - Thawarkar, Sachin; Nirmale, Trupti C; More, Sahebrao; Ambekar, Jalindar D; Kale, Bharat B; Khupse, Nageshwar D (Langmuir, 2019)
In this work, a fresh approach has been proposed for the efficient transfer of gold nanoparticles (AuNPs) from an aqueous to organic phase by the metathesis reaction or anion exchange reaction. Here, we synthesized ionic liquid 1-butyl 3-hexadecyl imidazolium bromide [C(4)C1(6I)m]-Br-stabilized AuNPs which exhibit excellent stability in solution. Transfer of Au@[C(4)C(16)Im]Br from an aqueous to organic phase was investigated by the metathesis reaction with different hydrophobic ionic liquid-forming salts such as LiNTf2, LiClO4, and KPF6. The anionic exchange process in ionic liquids at the AuNP surface to make hydrophilic to hydrophobic AuNPs is demonstrated. It was found that hydrophobic ionic liquids provide the most effective transfer of AuNPs from the aqueous to organic phase. Interestingly, we have noticed no change in color, size, and shape of AuNPs for more than a month, indicating more efficient transfer of AuNPs in organic solvents, which remained stable for over a month. The ionic liquids with anions NTf2-, ClO4-, and PF6- make the AuNP surface hydrophobic, indicating their good dispersibility in nonpolar solvents. Finally, these AuNPs exhibit excellent sensitivity toward the refractive index of organic solvents, which is correlated with the surface plasmon resonance (SPR) lambda(SPR) bands.